The Person in Narrative Therapy - Guilfoyle, M. author. aut Link
VII, 227 p.
Keywords: This book argues that narrative practice does not have a coherent formulation of personhood in the way one finds in other fields, such as psychoanalysis and cognitive-behavioural therapy. It examines the post-structural principles that underpin narrative practice, which make available powerful conceptual tools for theorizing the person.